2020
DOI: 10.7759/cureus.8933
|View full text |Cite
|
Sign up to set email alerts
|

The Myth of Colchicine in Treating Myopericarditis: Case Report and Literature Review

Abstract: Myopericarditis is inflammation of the pericardium with concurrent myocardial involvement. The clinical presentation of myopericarditis is often with varying degrees of cardiac symptomatology. Its etiology is often idiopathic, but it may also be related to infectious and inflammatory prodrome. Symptoms are proportional to the extent and pattern of myocardial involvement. Many are diagnosed sub-clinically during the management of other systemic illnesses. Echocardiography and cardiac magnetic resonance imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Myopericarditis is inflammatory pericarditis and myocardium culminating in myocardial cellular damage [ 2 , 8 ]. This condition is generally evaluated and treated as pericarditis, but when severe/prolonged ventricular dysfunction is found, it is called perimyocarditis [ 2 ]. Perimyocarditis must be evaluated and treated as myocarditis [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Myopericarditis is inflammatory pericarditis and myocardium culminating in myocardial cellular damage [ 2 , 8 ]. This condition is generally evaluated and treated as pericarditis, but when severe/prolonged ventricular dysfunction is found, it is called perimyocarditis [ 2 ]. Perimyocarditis must be evaluated and treated as myocarditis [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Myocarditis can cause ST-elevation on ECG; the more specific ECG changes for myocarditis include localized ST-elevation in inferolateral and anterolateral leads with concordant reciprocal depression, convex ST-segment, new Q wave, and prolonged QT interval [ 2 ]. A study showed that patients with acute myocarditis might also have AV block [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations